A Multi-core Heterogeneous Programmable Automation Controller System of Construction Machine - WANG Guoqing; YE Hong; Qu Jin; YANG Huaxin; LIU Chenghuan (Institute of Advanced Engineering and Science, 2013)
There are two main issues, high cost and interrupt response delay for current PACs (programmable automation controllers) which are using high frequency single-chip microprocessors and commercial RTOS (real-time operating system) working by switching the tasks and interrupts. To solve these problems, a new low-cost multi-core heterogeneous PAC structure was proposed. Based on the traditional front-end of interrupt service without interrupt switching delay and the division & deployment of multi real-time tasks. We implemented a new programming language Engineer C including its syntax, compiler and an integrated development environment, which can dynamically divide the multi tasks and deploy the division to single low-cost microcontroller, then built the hardware prototype, which consists of a digital signal board, an analog signal board and a motion control board, every board has its microcontroller and communicates each other by an enhanced SPI bus. Testing results show the hardware prototype and IDE can be provided as a low-cost PAC solution for construction machine. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3802